Structural characterization of a sulfated polysaccharide from Gracilariopsis lemaneiformis and its potentiation of cisplatin antitumor activity in Colon-26 carcinoma tumor-bearing mice by inducing ferroptosis. Issue 8 (28th March 2023) - Cai, Bingna; Luo, Lianxiang; Chen, Xiaodan; Zhao, Xiangtan; He, Jiake; Chen, Hua; Wan, Peng; Chen, Deke; Pan, Jianyu
Abstract : The G. lemaneiformis polysaccharide GP90 potentiates chemotherapy sensitivity by targeting the transferrin receptor and SLC7A11/Gpx4 pathway to induce ferroptosis. Abstract : Ferroptosis, a form of regulated cell death caused by iron-mediated lipid peroxidation, has become a potential strategy to overcome drug resistance and improve the efficacy of traditional cancer treatments. In this study, we investigated whether treatment with the combination of Gracilariopsis lemaneiformis polysaccharides and cisplatin (CP) potentiated the antitumor activity in a Colon-26 carcinoma tumor-bearing mouse model by ferroptosis activation. The G. lemaneiformis polysaccharide GP90 was mainly composed of (1→3) linked 4- O -sulfate-β-d -galactose and (1→4) linked 3, 6-anhydro-α-l -galactose with a molecular weight of 12.45 kDa. Compared with the CP group, the combination of GP90 and CP significantly suppressed tumor growth. Based on the transcriptomic and metabolomic analyses of tumor tissue, GP90 enhanced the antitumor effect of CP by promoting ferroptosis and regulating ferroptosis-related metabolic pathways. Moreover, the accumulation of 4-hydroxy-2-nonenal (4-HNE) and down-regulation of the expression of solute carrier family 7 member 11 (SLC7A11) and glutathione peroxidase 4 (Gpx4) were verified by immunohistochemistry staining. Finally, gene set enrichment analysis showed that positive immunoregulatory pathways were significantly enriched in the GP90 and CP combination group. Our results indicate that GP90 potentiates chemotherapy sensitivity by targeting the transferrin receptor and SLC7A11/Gpx4 pathway to induce ferroptosis, which might be a useful therapeutic target in colorectal cancer patients.